INVESTIGATION OF A DC TRACTION MOTOR IN THE SERIES EXCITATION GENERATOR MODE - Shpika, М.; Herasymenko, V.; Kostenko, I.; Skurikhin, V. (Municipal economy of cities. Series: «Economy science», 2024)
The article analyses electrical braking systems with direct current motors. It develops an experimental setup for studying the self-excitation of a traction motor. The research demonstrated the feasibility of implementing electrical braking systems with motors operating in the series excitation generator mode.